Anatomical Shaping for Zirconia Custom Implant Abutment to Enhance Anterior Esthetic: A Clinical Technique - Mohammed Alshehri; Mohammed Alghamdi; Abdullah S. Alayad (Hindawi Limited, 2020)
Abutments are used in dentistry to attach dental crowns to dental implant. Currently, zirconia custom abutment is the one which is mostly used in restorations, since it offers several advantages, especially better esthetics and prevention from infection. Several innovations are done in the implant designs and procedures to achieve better esthetics. Computer-aided design & computer-aided manufacturing (CAD/CAM) system is widely used innovative technology in dentistry. This technology offers custom implants that help to achieve better esthetics and good internal fit. This procedure used a novel technique of anatomical modification of the final abutment incisal edge from straight anatomical edge to irregular one with a mamelon-incisal effect to enhance esthetic, shade matching, and anatomical replication of incisal structure that resembles the natural incisor. Usually, dental technicians will perform facial and incisal cut-back and apply porcelain layers to the crown in order to reproduce the translucency and the other optical effects that most closely match that of natural dentin and enamel, especially at the incisal edge. These optical effects will make the prosthetic crown look more natural and esthetically pleasant. By this presented technique will help the dental technician to achieve highly esthetic crown with completely digital workflow without the need for porcelain layering. The procedure was also followed up to 3, 6, and 12 months after the surgery and found no complications or complaints from the patient and esthetically satisfied.